To solve the system of equations, we'll use the method of substitution.
From the first equation, we have x = 6y - 3.
Substituting x in the second equation, we have 2(6y - 3) + 7y = 13.
Expanding the equation, we get 12y - 6 + 7y = 13.
Combining like terms, we have 19y - 6 = 13.
Adding 6 to both sides, we get 19y = 19.
Dividing both sides by 19, we find that y = 1.
Substituting y = 1 into the first equation, we have x = 6(1) - 3 = 6 - 3 = 3.
Therefore, the solution to the system of equations is x = 3 and y = 1.
Solve the system of equations.%0D%0Ax=6y−3%0D%0A2x+7y=13(1 point
1 answer